Research into Design for a Connected World Proceedings of ICoRD 2019 Volume 1 - Chakrabarti, Amaresh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book showcases cutting-edge research papers from the 7th International Conference on Research into Design (ICoRD 2019) - the largest in India in this area - written by eminent researchers from across the world on design processes, technologies, methods and tools, and their impact on innovation, for supporting design for a connected world. The theme of ICoRD'19 has been "Design for a Connected World". While Design traditionally focused on developing products that worked on their own, an emerging trend is to have products with a smart layer that makes them context aware and responsive, individually and collectively, through collaboration with other physical and digital objects with which these are connected. The papers in this volume explore these themes, and their key focus is connectivity: how do products and their development change in a connected world? The volume will be of interest to researchers, professionals and entrepreneurs working in the areas on industrial design, manufacturing, consumer goods, and industrial management who are interested in the use of emerging technologies such as IOT, IIOT, Digital Twins, I4.0 etc. as well as new and emerging methods and tools to design new products, systems and services.
Part I: Design Theory and Research Methodology -- Part II: Human factors in Design -- Part III: Design for X (Safety, Manufacture & Assembly, Cost , Reliability etc.) -- Part IV: Enabling Technologies & Tools (Computer Aided Conceptual Design, Virtual Reality, Haptics, etc) -- Part V: Design Management, Knowledge Management and Product Life Cycle Management , Design Analytics -- Part VI: Applications in Practice (Automotive, Aerospace, Biomedical Devices, MEMS, etc.) -- Part VII: Design Collaboration and Communication.
Keywords: Engineering design; Manufactures; Security systems; Engineering Design; Machines, Tools, Processes; Security Science and Technology